Rifamycin derivatives active against pathogenic rapidly-growing mycobacteria. Issue 16 (15th August 2019) - Combrink, Keith D.; Ramos, Andrea Ramirez; Spring, Stephanie; Schmidl, Sebastian; Elizondo, Kira; Morin, Petronilo; De Jesus, Bryant; Maurer, Florian P.
Graphical abstract: C25 carbamate rifamycin derivatives show potent activity against rapidly growing mycobacterium, RGM, including Mycobacterium abscessus and are not substrates for the bacterial modifying enzyme Arr. Rifampin has no activity against RGM and is heavily modified by RGM. Abstract: Infections due to rapidly growing mycobacteria (RGM), and in particular the RGM species Mycobacterium abscessus (Mab), are very difficult to treat and reports on novel therapeutic options are scarce. A hallmark of all pathogenic RGM species is their resistance to the four first-line drugs used to treat infections with Mycobacterium tuberculosis including rifampicin. This study demonstrates that modification of the rifampicin scaffold can restore rifampicin activity against the three most commonly isolated pathogenic RGM species including Mab . We also note that the structure-activity relationship for Mab is different as compared to the non-pathogenic RGM species Mycobacterium smegmatis .